Islamic Economics Students' Perceptions of Digital Philanthropy Platforms and Their Impact on Islamic Economics Students' Interest in Donating - Habibah Nurul Fitri Fadhillah; Lucky Engraini Fitri; Ridhwan . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Islamic Economics Students' Perceptions of Digital Philanthropy Platforms and Their Impact on Islamic Economics Students' Interest in Donating